New investigations of the Hjortspring boat: Dating and analysis of the cordage and caulking materials used in a pre-Roman iron age plank boat - Mikael Fauvelle; Boel Bengtsson; Olof Pipping; Mikkel Hollmann; Martin Nordvig Mortensen; Peter Toft; Sahel Ganji; Ashely Green; Christian Horn; Stephen Hall; Flemming Kaul; Johan Ling (PLoS ONE, 2025)
The Hjortspring boat is the only intact example of a prehistoric sewn plank boat ever found in Scandinavia. Built from lime wood planks lashed together with cordage, the boat represents the maritime technology used by some of Northern Europe’s earliest seafarers. This article reports new analysis of the cordage and caulking material used in the construction of the Hjortspring boat. We provide the first ever direct date for the boat based on materials from the original excavation finds, with lime bast cordage from the boat carbon dated to between 381 and 161 BCE. We report the results of GC-MS analysis of the material used to caulk the boat, which shows that it was made from a mixture of animal fat and pine pitch. We argue that the use of pine pitch in the boat’s construction indicates that the boat was not built on the Jutland peninsula and instead came from a region with more abundant pine forests. Based on the dispersal of pine forests in Northern Europe during the first millennium BCE, we propose the Baltic Sea Region east of Rügen and Scania as a likely source for the boat and its crew. We also analyze intact cordage fragments and imprints of cordage on caulking material in order to describe the sewing and rope-making techniques that were used to construct the boat. Finally, we report on the discovery of a partial human fingerprint found on a fragment of caulking material. This remarkable fingerprint provides a direct link to the ancient seafarers who used this boat. Together, these results shed new light on methods and materials used to build Scandinavia’s first plank boats and raise new questions regarding our understanding of early maritime societies in Northern Europe.